Conservation and Diversity of Historical Monuments: A Comprehensive Study - Basavaraj Hullur (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Historical monuments represent the architectural legacy, cultural memory, and civilizational identity of a nation. Their preservation is essential not only for historical continuity but also for strengthening the collective sense of belonging among present and future generations. This article examines the concepts, principles, and practices of monument conservation, along with government initiatives, technical mechanisms, and public–private partnerships that have significantly contributed to heritage protection, with specific reference to Karnataka.